2017
DOI: 10.1038/s41598-017-12973-5
|View full text |Cite
|
Sign up to set email alerts
|

The GBAP1 pseudogene acts as a ceRNA for the glucocerebrosidase gene GBA by sponging miR-22-3p

Abstract: Mutations in the GBA gene, encoding lysosomal glucocerebrosidase, represent the major predisposing factor for Parkinson’s disease (PD), and modulation of the glucocerebrosidase activity is an emerging PD therapy. However, little is known about mechanisms regulating GBA expression. We explored the existence of a regulatory network involving GBA, its expressed pseudogene GBAP1, and microRNAs. The high level of sequence identity between GBA and GBAP1 makes the pseudogene a promising competing-endogenous RNA (ceRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 58 publications
2
66
0
Order By: Relevance
“…The functional impact of several of these miRNAs on brain function has been illustrated. Last, we have also included miR‐22‐3p in the analysis as it targets GBA messenger RNA (mRNA) and is highly expressed in the brain …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The functional impact of several of these miRNAs on brain function has been illustrated. Last, we have also included miR‐22‐3p in the analysis as it targets GBA messenger RNA (mRNA) and is highly expressed in the brain …”
Section: Methodsmentioning
confidence: 99%
“…Last, we have also included miR-22-3p in the analysis as it targets GBA messenger RNA (mRNA) and is highly expressed in the brain. 30…”
Section: List Of Brain-enriched Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…GBA encodes lysosomal glucocerebrosidase and its mutations are associated with Parkinson's disease. Recently, Tang et al (2017b) demonstrated that GBAP1, a pseudogene of GBA, acted as a ceRNA for GBA by competing with miR-22-3p.…”
Section: Gbap1mentioning
confidence: 99%
“…Although formerly considered a noncoding gene, recent data not only show evidence of mRNA expression but that genetic variation in GBAP1 expression could determine expression of the GBA1 gene by acting as a competing antagonist mRNA. 155 Similarly, evidence that variation in upstream promoter regions of the GBA1 gene may modulate GCase activity is available. 156 Interestingly, there is some evidence that the haplotype of the L444P mutation may alter the penetrance of GDassociated alleles, and this may play a significant role in the penetrance of other mutations.…”
Section: Early Detection Of Conversionmentioning
confidence: 99%